Under Pressure: A Comparative Study of Botrytis cinerea Populations from Conventional and Organic Farms in Cyprus and Greece - Makris, Georgios; Nikoloudakis, Nikolaos; Samaras, Anastasios; Karaoglanidis, Georgios S.; Kanetis, Loukas (My University, 2022)
The highly heterogeneous nature of Botrytis cinerea provides adaptive benefits to variable environmental regimes. Disentangling pathogen population structure in anthropogenic agroecosystems is crucial to designing more effective management schemes. Herein, we studied how evolutionary forces exerted in different farming systems, in terms of agrochemicals-input, shape B. cinerea populations. In total, 360 B. cinerea isolates were collected from conventional and organic, strawberry and tomato farms in Cyprus and Greece. The occurrence and frequency of sensitivities to seven botryticides were estimated. Results highlighted widespread fungicide resistance in conventional farms since only 15.5% of the isolates were sensitive. A considerable frequency of fungicide-resistant isolates was also detected in the organic farms (14.9%). High resistance frequencies were observed for boscalid (67.7%), pyraclostrobin (67.3%), cyprodinil (65.9%), and thiophanate-methyl (61.4%) in conventional farms, while high levels of multiple fungicide resistance were also evident. Furthermore, B. cinerea isolates were genotyped using a set of seven microsatellite markers (simple sequence repeat [SSR] markers). Index of association analyses (Ia and rBarD) suggest asexual reproduction of the populations, even though the mating-type idiomorphs were equally distributed, indicating frequency-dependent selection. Fungicide resistance was correlated with farming systems across countries and crops, while SSRs were able to detect population structure associated with resistance to thiophanate-methyl, pyraclostrobin, boscalid, and cyprodinil. The expected heterozygosity in organic farms was significantly higher than in conventional, suggesting the absence of selective pressure that may change the allelic abundance in organic farms. However, genetic variance among strawberry and tomato populations was high, ranking host specificity higher than other selection forces studied.
Keywords: Botrytis cinerea; Disease control and pest management; Fungal pathogen; Fungicide resistance; Genetic diversity; Gray mold; Microsatellites; Population genetics